Reductive Leaching Of Synthetic Manganese Ore Using Bamboo Sawdust As Reducing Agent- A Comparison Between Direct Hydrolysis-Leaching Process And Simultaneous - Kimberly, Tay Shu Yen (Universiti Sains Malaysia, 2017)
This research was carried out to investigate the effects of concentration of sulfuric acid and stirring speed on the reductive leaching of synthetic manganese ore using bamboo sawdust as reducing agent, comparing the direct hydrolysis-leaching process and simultaneous hydrolysis-leaching process. Prior to the experimental work, sample preparation and characterisation analysis were carried out to understand the crystallinity, surface morphology, particle size distribution and ash content of the BSD sample. The results obtained from the characterisation studies further suggests that BSD is a good carbohydrate source and suitable to be used as a reducing agent in the reductive leaching process. The experimental work is based on the full factorial design using 23 + 1. The three variables in the reductive leaching experiment are concentration of sulfuric acid, stirring speed and hydrolysis-leaching method. Reducing sugars in solution form is obtained from the hydrolysis process. The manganese recovery was estimated volumetrically by EDTA titration using thymolphthalexone indicator. Based on the statistical model generated from the ANOVA, it was found that concentration of sulfuric acid (X1) has the most significant effect of the reductive leaching of synthetic manganese ore in terms of recovery followed by the stirring speed (X2). This study also shows that different hydrolysis-leaching method does not have a significant effect on the overall reductive leaching of synthetic manganese ore. Approximately 99% of manganese can be recovered from synthetic manganese ore using BSD as reducing agent under the optimum conditions of 4 M concentration of sulfuric acid, 400 rpm stirring speed, 100°C reaction temperature, 6 hours reaction time, 10% pulp density and -75 μm particle size.